2011
DOI: 10.1186/1471-230x-11-89
|View full text |Cite
|
Sign up to set email alerts
|

The prone 12 o'clock position reduces ileal intubation time during colonoscopy compared to the left lateral 6 o'clock (standard) position

Abstract: BackgroundIleal intubation is the gold standard for a complete colonoscopy. However, despite evidence of clinical benefit ileoscopy is not always attempted due to perceived technical difficulty. Our aim was to compare time taken for ileal intubation using a new position-the prone 12 o'clock position (PP) with the standard method (left lateral 6 o'clock position-LLP).MethodsWe performed a pilot study using fluoroscopy to determine the best patient position for ileal intubation. This was the prone 12 o'clock pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…One study that used fluoroscopy to document the orientation of the colonoscope found that prone positioning straightened that orientation and facilitated intubation of the terminal ileum [11]. This study focused on ileal (not cecal) intubation, however, and the report provides no information on the BMI of study participants.…”
Section: Discussionmentioning
confidence: 96%
“…One study that used fluoroscopy to document the orientation of the colonoscope found that prone positioning straightened that orientation and facilitated intubation of the terminal ileum [11]. This study focused on ileal (not cecal) intubation, however, and the report provides no information on the BMI of study participants.…”
Section: Discussionmentioning
confidence: 96%
“…The TIIT was defined as the time required for the colonoscope end to be maneuvered from the cecum to the intubation of the terminal ileum. 20 Intubation of the terminal ileum was confirmed by photographic documentation of apparent villi in the terminal ileum by water-filling or using the narrow-band imaging method. 21 Cases where the terminal ileum could not be intubated were not included in the analysis of TIIT.…”
Section: Methodsmentioning
confidence: 99%
“…The prone position showed superior results for ileal intubation. [29][30][31]. To improve the performance in an endoscopy unit, the quality of colonoscopy was assessed.…”
Section: Introductionmentioning
confidence: 99%